2015
DOI: 10.1097/jom.0000000000000577
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Endocrine Disruption Activity of Deposits on Firefighting Gear Using a Sensitive and High Throughput Screening Method

Abstract: Objective Adverse health outcomes related to exposure to endocrine disrupting chemicals (EDCs), including increased incidences of coronary heart disease, prostate and testicular cancers, and birth defects have been reported in firefighters or their offspring. We, therefore, measured the estrogenic and antiestrogenic activity of extracts of used firefighter gear to assess exposure to these agents. Methods Extracts and known chemical contaminants were examined for estrogenicity and antiestrogenicity in yeast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…In 2014, phthalate diesters as major contaminants of soiled firefighter gear have been studied [24,25]. Stevenson et al [25] in their study also claim that new glove and hood extracts made from materials containing phthalates used by firefighters showed that significant estrogenic activity resulted in perturbation of hormone homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2014, phthalate diesters as major contaminants of soiled firefighter gear have been studied [24,25]. Stevenson et al [25] in their study also claim that new glove and hood extracts made from materials containing phthalates used by firefighters showed that significant estrogenic activity resulted in perturbation of hormone homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, phthalate diesters as major contaminants of soiled firefighter gear have been studied [24,25]. Stevenson et al [25] in their study also claim that new glove and hood extracts made from materials containing phthalates used by firefighters showed that significant estrogenic activity resulted in perturbation of hormone homeostasis. Phthalates contained in firefighters' gear (either during production or during burning) are a worrying finding because phthalates are lipophilic, and the extreme heat helps phthalates enter through the skin and could modify their health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is only one report of the association of borderline-low testosterone with low left ventricular thickness from the annual screening data [ 10 ]. Other authors studied the estrogenic and antiestrogenic activity of the deposits on firefighters gear [ 11 ]. Serious lack of studies of testosterone levels in firefighters does not allow to understand how testosterone levels can affect burnout and how that can be used for screening and proper work placement.…”
Section: Discussionmentioning
confidence: 99%
“…Besides metals and dyes, important clothing contaminants are formaldehyde and formaldehyde releasers, dioxin, perfluorinated compounds, flame retardants, phthalates and other plasticizers such as diisodecyclmaleate, and pesticides used in shipment [27][28][29][30]. These and other chemicals have been associated with serious health consequences in laboratory and epidemiologic studies [31,32].…”
Section: Discussionmentioning
confidence: 99%